Space, Time, and Identity in Sir Gawain and the Green Knight (ENTHYMEMA, 2025)
Sir Gawain and The Green Knight explores the transformation of Gawain’s identity through his quest, where time and space play crucial roles. The narrative juxtaposes brief, action-packed episodes with extended periods of stillness, emphasizing Gawain's passive heroism. The circular structure of the journey symbolizes a return to the self, yet transformed through encounters with the other. The use of Paul Ricœur's theory about narrative identity highlights the significance of Gawain's wounds as paths to self-recognition. The comparison with David Lowery’s 2021 film adaptation reveals contemporary concerns with identity and otherness.
Keywords: Narrative Identity; Circular Structure; Passive Quest; Temporal Rhythm; Self-Recognition